The Economic Function of Doctoral Programs in Accounting: Alternative Theories and Educational Implications. - Johnson, Steven B. (The Accounting Review, 1985)
ABSTRACT: Differences in faculty beliefs as to the economic function of accounting, doctoral programs may contribute to the heterogeneity of educational policies and practices that exist across programs. Many accounting doctoral program policy makers appear to adhere, explicitly or implicitly, to either the "human capital" or "screening" theories of occupational licensing/certification. This study compares these two theories and evaluates the educational policies and practices they imply. The analysis suggests that, when relied upon to provide perspective in resolving policy questions, rather than in an orthodox fashion, these theories can provide useful guidance to accounting doctoral program policy makers.